Sagebrush trail - Shaefer, Armand, 1898-1967; Parsons, Lindsley, 1905-1992; Wayne, John, 1907-1979; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1933)
A young cowboy finds himself behind bars, wrongly accused of a robbery. Seeing his chance, he escapes to bring the guilty bandit to justice and clear his name.
Originally released as a motion picture in 1933.
"A Paul Malvern production."
John Wayne, Nancy Shubert, Lane Chandler, Yakima Canutt, Wally Wales, Art Mix, Bob Burns.
Cinematographer, Archie Stout; editor, Carl Pierson.
In English; also available an Spanish dubbed version.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Cowboys -- Drama; False imprisonment -- Drama; Western films; Feature films; Internet videos; Streaming video